Anti-VEGF immunotherapy with HEBERSaVax suppresses melanoma growth and metastasis via angiogenesis blockade and enhanced T-cell infiltration - Morera-Díaz, Yanelys; García-Sanmartín, Josune; Canaán-Haden, Camila; Bequet-Romero, Mónica; Gonzalez-Moya, Isabel; Ayala-Ávila, Marta; Tadic, Srdan; Garrido, Pablo; Narro-Íñiguez, Judit; Fuentes-Morales, Dasha; Bernáldez-Sarabia, Johanna; Valdovinos-Navarro, Blanca J.; et al. (Frontiers in Immunology, 2025)
IntroductionTargeting tumor angiogenesis through vascular endothelial growth factor (VEGF) blockade represents a promising strategy for melanoma treatment. Here, we evaluate the therapeutic potential of HEBERSaVax, an anti-VEGF active immunotherapy, in aggressive B16-F10 syngeneic melanoma models.MethodsThe antitumor activity of HEBERSaVax, formulated with aluminum phosphate adjuvant, was evaluated in C57BL/6 mice using two distinct B16-F10 melanoma models (i): subcutaneous inoculation to assess primary tumor growth inhibition, and (ii) intravenous inoculation to quantify lung metastasis suppression. Tumor vasculature and microenvironment changes were analyzed via immunohistochemistry (CD31, α-SMA, CD4, CD8).ResultsHEBERSaVax significantly reduced primary tumor volume and weight in subcutaneous implants compared to adjuvant controls. Histopathological analysis revealed potent angiogenesis inhibition, decreased CD31+ vessel density, and vascular remodeling. Concomitant with tumor control, we observed changes in the tumor microenvironment, including a reduction in α-SMA+ pericytes and an increase in the infiltration of CD4+ and CD8+ T cells. In the metastatic model, HEBERSaVax-treated mice showed fewer pulmonary nodules versus controls.DiscussionOur results demonstrate that HEBERSaVax mediates dual antitumor efficacy by simultaneously suppressing VEGF-dependent angiogenesis and promoting immune-related changes in the melanoma microenvironment. These findings support the further development of HEBERSaVax as a promising active immunotherapy for VEGF-driven advanced melanoma.